Hierarchical bioglass scaffolds: Introducing the "milky way" for templated bioceramics - Onna, Diego Ariel (2015)
Free standing hierarchical bioglass scaffolds were prepared by the ISISA (ice-segregation-induced self-assembly) method. Commercial low-cost precursors such as Ludox® HS-40 and cow milk were employed as the source of SiO2 and biominerals (Ca(ii), P(v), Na(i) and K(i)), respectively. Then, in a single macroscopic piece, three levels of porosity coexist due to the simultaneous templating effect of ice (macropores), milk (50-200 nm mesopores) and the voids left between preformed Ludox® nano building blocks (2-5 nm mesopores). These low cost and green biological nanotemplates, coupled with the ISISA texturing method, allows the preparation of free standing bioglass monoliths, with hierarchical porosity. The effect of the main preparative variables on the final texture is explored; in vitro biomineralization revealed a well-distributed hydroxyapatite-like nanoparticulated layer within 24 h of exposure to a simulated body fluid.